Leveraging Agri-Food Strategies Through SWOT Analysis Embedded Into the Business Model Canvas: Insights from the Seaweed Industry in East Nusa Tenggara Province, Indonesia - Wardono, Budi; Prabakusuma, Adhita Sri; Yusuf, Risna; Yulisti, Maharini; Mulyawan, Irwan; Luhur, Estu Sri (Unversitas Muhammadiyah Mataram, 2024)
Abstract: The seaweed industry in the agri-food sector faces significant challenges, such as fluctuating market demand, environmental constraints, and economic pressures, requiring strategic and adaptive solutions. This study explored the integration of SWOT analysis with the Business Model Canvas (BMC) as an innovative approach for strategic planning in the seaweed industry in East Nusa Tenggara (NTT) Province, Indonesia. A mixed-method approach was employed, combining qualitative and quantitative data collection. Qualitative data were gathered through purposive sampling through focus group discussions and in-depth interviews with key stakeholders and experts. Quantitative analysis was conducted using the Analytical Hierarchy Process (AHP) to prioritize strategies derived from the SWOT-BMC integration. The SWOT factors were embedded into the BMC framework to analyze strategic elements. The AHP results revealed that the highest priority strategy (W-O) emphasized innovation and infrastructure improvement through collaboration with government and private stakeholders (weight of 0.122). This strategy focuses on modernizing processing facilities and enhancing supply chain management to ensure consistent product quality and increase capacity to meet global market demand. In contrast, leveraging government support and local natural resources (S-O) was ranked lower in priority (weight of 0.081). Key BMC elements—key activities, key resources, and value propositions—were strengthened by incorporating W-O, S-T, and W-T strategies. This integrated SWOT-BMC approach provides a comprehensive framework for the seaweed industry to drive innovation, enhance competitiveness, and promote a sustainable food system. The study’s practical implications highlight the importance of targeted investments in technology and infrastructure to ensure long-term success in the global market.